Hospital Patient Data Security Evaluation to Achieve SDGs 3.8.1 “Good Health and Wellbeing” - Rasyad, Muhammad Fakhri; Lubis, Ratna Lindawati (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
One of the major problems in health digitalization is data security, especially in hospitals, which are highly vulnerable to cybercrime, such as patient data leaks. This concern also affects Permata Cirebon Hospital in its efforts to achieve quality healthcare services aligned with SDG 3.8.1. This research aims to evaluate patient data security based on existing hospital policies and procedures. A qualitative method with an evaluative approach was used, involving interviews with four informants, observations, and documentation reviews. Data were analyzed thematically to identify patterns and issues. The evaluation found that Permata Cirebon Hospital has implemented several key measures, including VPN usage, access restrictions, and dashboard-based monitoring. However, significant gaps remain. Incident reporting is conducted but lacks standardized procedures and is largely reactive. The hospital does not perform routine audits, and evaluations are not guided by specific performance indicators. Staff training on data security is minimal and inconsistent, raising concerns about human error risks. Additionally, cryptographic techniques for protecting sensitive data remain underdeveloped. These findings indicate that while initial efforts toward securing patient data exist, they are insufficient to meet modern data security standards. The research recommends enhancing system resilience through blockchain-based encryption, establishing a formal incident response protocol, conducting regular audits, and providing comprehensive training for staff. Strengthening these areas is essential to ensure sustainable, secure, and high-quality healthcare services.